PERBEDAAN KARAKTERISTIK PADA BROWNIES DENGAN MENGGUNAKAN BUBUK KAKAO DAN BUBUK KOKOA - Kurnianingsih kurnianingsih; Annisa Eva Salsabila Anwar; Nuzul Aulya Safawi; Sabilla Aditya Prameswari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
The comparation of brownies using cacao powder and cocoa powder are expected to be the standart to determine the best brownies. Purpose of the riset 1). To know the making of brownies using cacao powder and cocoa powder 2). To know the characteristic brownies using cacao powder and cocoa powder 3).To know the acceptability Panelist toward brownies using cacao and cocoa powder. Method of the riset is using literature method, documentation, experiment and hedonic test. The making of brownies cacao and cocoa experiment based on Program Study Culinary Art Academy Kesejahteraan Sosial Ibu Kartini Laboratory. Sultan Agung Street No.77 sub-distric Gajah Mungkur, Semarang. The percentage addition of cacao and cocoa powder in the making of brownies are 33% from weight of the flour. Result of the riset shown brownies with addition cacao and cocoa powder has sensory characteristics as sweet, bitter, a little bit savory, the colour is dark brown, the texture is solid and soft, the smell is like the characteristics of brownies. The acceptability of the Panelist with addition of cacao and cocoa powder in the brownies shown that the Panelist likes the brownies with cacao powder addition. Then we can conclude addition of the right choco powder for brownies is cacao powder.